Simulasi Kinerja Persimpangan Sebagai Upaya Preventif Kemacetan Pada Simpang Kominfo-Kencana-Kodim di Kabupaten Grobogan - Faqih, Fajar; Tama, Yuanda Patria (Jurnal Sosial Terapan, 2024)
Based on data from the Central Java Provincial Statistics Agency, the average vehicle growth in Grobogan Regency is 4.9% per year. This shows that each year more and more vehicles are used by the people. In addition, based on Presidential Regulation No. 60 of 2022 the Purwodadi Urban Area which is included in the Kedungsepur National Strategic Area is planned to be developed into an international Center for Economic Activities. It is feared that in the next few years the traffic flow can no longer be controlled resulting in severe congestion. Preventive efforts are important so that steps in problem-solving efforts can be taken before the problem itself occurs in the future. This is what wants to be applied to the intersection at the R. Suprapto - MT. Haryono Grobogan Regency because this road is located in the Central Business District (CBD) area. Efforts to improve intersection performance are carried out in 2 stages, namely during the existing year and the plan year, to find out the conditions of the plan year, traffic forecasting is carried out. This research uses the basic formula from the Indonesian Road Capacity Guidelines (PKJI 2023). Further comparisons are made to determine the best proposals that can be applied to each intersection.From the analysis calculation, it is known that the performance of the three intersections in 2023 has improved compared to the existing conditions after the best recommendation is made. Kominfo intersection which previously had a delay time of 27.02 sec/pcu to 12.94 sec/pcu, kencana intersection from 38.68 sec/pcu down to 13.18 sec/pcu, and kodim intersection with an existing delay time of 15.94 sec/pcu down to 12.58 sec/pcu. Furthermore, in 2029 handling efforts were again carried out to maintain the performance of each intersection to remain good.